Development of Digital Teaching Materials for Procedure Texts With Theme of Malay Culinary Typical Based on Book Creators for Sinar Husni Private Senior High School - Ichsan Ardhian, Mhd; Rahmat Kartolo (International Journal of Educational Research Excellence (IJERE), 2025)
This research aims to develop a teaching material product, specifically digital teaching materials for procedure texts with the theme of distinctive Malay cuisine, based on Book Creator. It is expected that this product can improve the quality of learning. This research is a development research or research and development that employs the ADDIE development procedure. The product of this research is digital teaching material for procedure texts with the theme of distinctive Malay cuisine based on Book Creator for Class XI of Senior High School. The subjects of this research include material expert validators, media (Design) expert validators, and Indonesian language teachers of Class XI at Sinar Husni Private High School. The research steps consist of analysis, design, development, implementation, and evaluation. The research instruments used in this study include student needs questionnaires, teacher needs questionnaires, material expert validation, media expert validation, pretest and posttest, and responses from the subject teachers. The results of this research indicate that the developed digital teaching materials, using the ADDIE procedure, obtained validation results with a "very feasible" qualification, with scores from the material expert validator of 89.6% and the media expert validator of 96.7%. Furthermore, the effectiveness results obtained from the digital teaching materials show good effectiveness, with a subject teacher response score of 93.3% with a "very good" qualification, and the pretest and posttest of students showed an increase in the average score from 69.8 to 87.6. The Normalized Gain (N-Gain) calculation yielded an average value of 0.59 or 59%, which falls into the "moderately effective" category. Therefore, it can be concluded that the digital teaching material product developed in this research is very suitable for use by students in the learning process